1979
DOI: 10.1161/01.res.45.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension following denervation of aortic baroreceptors in unanesthetized dogs.

Abstract: SUMMARY After cervical aortic nerve section, mean arterial pressure in the unanesthetized dog increased by an average of 7.4 mm Hg. Following a more extensive denervation of aortic arch receptors by section of intrathoracic vagal branches, arterial pressure increased by 16.7 mm Hg. The above changes were seen in the stable state after the effects of surgery had disappeared. In both cases carotid baroreceptors were functional. After administration of nitroglycerin and phenylephrine subsequent to either denervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 50 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…Vatner et al (1) suggested from studies in awake dogs that the aortic baroreceptors were more effective than the carotid baroreceptors in controlling heart rate. Similar findings in the dog were reported by Ito and Scher (2,3) in which chronic denervation experiments suggested that reflex heart rate responses are impaired to a greater extent by aortic baroreflex denervation than by carotid denervation. In contrast, Guo et al (4) have shown the carotid and aortic baroreceptors exert similar degrees of vagally mediated heart rate control in anesthetized rabbits during phenylephrine (PE)-induced' hypertension.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Vatner et al (1) suggested from studies in awake dogs that the aortic baroreceptors were more effective than the carotid baroreceptors in controlling heart rate. Similar findings in the dog were reported by Ito and Scher (2,3) in which chronic denervation experiments suggested that reflex heart rate responses are impaired to a greater extent by aortic baroreflex denervation than by carotid denervation. In contrast, Guo et al (4) have shown the carotid and aortic baroreceptors exert similar degrees of vagally mediated heart rate control in anesthetized rabbits during phenylephrine (PE)-induced' hypertension.…”
Section: Introductionsupporting
confidence: 88%
“…Fig. 3 and Table I summarize the responses of subjects [1][2][3][4][5][6][7][8][9][10] Table I), which was associated with a prolongation of HI from 1,068±58 to 1,297±69 ms (P < 0.05). This was an average gain in HI of 27.7 ms/mmHg increase in MAP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SD or V is one index of stability of AP. Since the value of SD was increased by sectioning afferent nerves from the baroreceptors [3,12,13,17], and decreased in the normotensive pressure range [15,17], the increase in SD represents reduced control ability of the baroreflex system. This accords well with the fact that an open-loop gain, a homeostatic index of the baroreflex system, was decreased by severing the carotid sinus, aortic or vagus nerves [10,11].…”
mentioning
confidence: 99%
“…Therefore, we can conclude that the overall control ability of the rapidly acting AP control system is not affected by aging within the range from 6 to 30 months. Distribution pattern of histogram has often been employed for estimation of variability of AP [3,12,13,15]. Distribution became wide after the baroreceptors had been denervated [3,12,131, whereas narrow distribution and an exaggerated mode imply increased control ability of the baroreflex system.…”
mentioning
confidence: 99%